Resilience and sustainability of traditional agroecosystems of Mexico: Totonacapan - Cuevas Coeto, Axayacatl; Vera Castillo, Yolanda Beatriz; Cuevas Sánchez, Jesús Axayacatl (Revista Mexicana de Ciencias Agrícolas, 2019)
In Mexico, traditional agricultural technology, resulting from the thousand-year accumulation of valuable experiences pertinent to the management, exploitation and selection under domestication of a wide range of ethno-resources, continues to be expressed in a wide area. However, due to various negative aspects of the acculturation process, its biological and cultural foundations are at serious risk. Considering the agroecosystem, the integral study unit leading to the understanding of the interrelations involved in the dynamics of its physical, biological and cultural components and having as objective, contribute to the understanding of the ecological and cultural dynamics evidenced in traditional agroecosystems of the Totonacapan. Through experiences derived from more than three decades of work in the region, some distinctive features of these agricultural production systems are described and analyzed, emphasizing the milpa and the mountain as spaces in which knowledge and attitudes related to the production and transmission of knowledge are generated and transmitted. perception, management, use and conservation of ethno-resources inherent to them. Quantitative information linked to the dynamics of this type of agricultural production systems is provided. The applied methods were based on the framework for the evaluation of natural resource management systems incorporating sustainability indicators (MESMIS), life cycle assessment (LCA), ethnobotanical exploration, as well as participatory observation. Based on the definition and evaluation of 15 indexes relevant to their resilience, a transdisciplinary work model is proposed, leading to the measurement of the degree of sustainability evidenced by them. The results indicate that the greater the biocultural legacy transmitted by their ancestors and the attachment of peasant families to it, the greater the ecological and cultural resilience of their agroecosystems and, consequently, the sustainability evidenced by them.
Keywords: agricultural production, conservation, ethno-resources.